2017
DOI: 10.1093/geronb/gbw153
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Incident Stroke Among Older Adults

Abstract: Among older adults, those who used to, but no longer, drink had higher risks of stroke, especially among women; current light drinkers had the lowest risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Quitting smoking limits the destruction of the periodontal tissues and leads to better clinical results [ 78 ]. Alcohol consumption is also more frequent in men who are stroke survivors compared to women [ 79 , 80 , 81 ], as in our study. The risk for periodontitis among men reporting regular alcohol intake previously proved dose-dependency [ 82 ].…”
Section: Discussionsupporting
confidence: 74%
“…Quitting smoking limits the destruction of the periodontal tissues and leads to better clinical results [ 78 ]. Alcohol consumption is also more frequent in men who are stroke survivors compared to women [ 79 , 80 , 81 ], as in our study. The risk for periodontitis among men reporting regular alcohol intake previously proved dose-dependency [ 82 ].…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, incidence of prefrailty in the FP-population was 34.4%. The difference between the two measures is considerable but consistent with published literature [ 39 , 40 ]. The meta-analysis on frailty incidence reported 4.6% pooled incidence of frailty among robust older adults aged 60 years and older during a median follow-up of three years.…”
Section: Discussionsupporting
confidence: 90%
“…Non-hazardous and hazardous alcohol use in old age showed decreased frailty risk compared to no alcohol use, even after adjustment for baseline disease and medication use; however, hazardous alcohol use showed smaller decrease than non-hazardous alcohol use (adjusted OR (95% CI): 0.68 (0.60-0.77) for nonhazardous use and 0.80 (0.68-0.93) for hazardous alcohol use). Similarly, when using frailty phenotype as the outcome measure, only non-hazardous alcohol use was associated with decreased frailty incidence, suggesting a U-shaped relationship, which has been proposed before [6,38,39]. Sub-analysis of our data using previous alcohol problems as additional cofactor showed that participants with previous alcohol problems (self-reported excessive drinking problem in the past) have significantly increased incidence of frailty compared to participants without previous alcohol problems, even after adjustment for several confounding factors.…”
Section: Discussionmentioning
confidence: 60%
“…This study also found that there was no significant relationship between the consumption of alcohol and the incidence of stroke. Other study reported that alcohol consumption can increase the risk of stroke (24,25), limited subjetc that dominated by ISH in elderly in this study may influence the result (26).…”
Section: Discussionmentioning
confidence: 52%